THE SOCIETY OF SPECTACLE AND RELIGIOUS AS CONSUMPTION (Fiep Bulletin - online, 2019)
This article was developed through a partnership between Masters researchers in Humanities, Cultures and Arts in aninterdisciplinary perspective in Marketing and Theology, aiming at analyzing Prosperity Theology in Brazil and its use as aninstrument for attracting new followers, as well as for their loyalty. The article concomitantly approaches the concepts of theSociety of the Spectacle, Society of Consumption and Information Society, considering the use of the means of communicationfor the propagation of the achievements of its followers. It has as theoretical reference the works of Debord, Slater, Mariano,Novaes, Baudrillard, Kotler and Armstrong in an analysis about the use of religiosity as a form of glamorization and spectacle witha comparative analysis with the biblical texts. The methodology is based on exploratory and bibliographical research that will bepertinent throughout the text. Through studies of prosperity as an instrument for the "conversion of souls" and for theempowerment of the individual within social groups in neoliberal models.
Keywords: Society of the Spectacle; Religiosity as Consumption; Brazilian Neopentecostalism